Pediatric providers’ views on participating in an HPV Vaccine Quality Improvement Intervention: a qualitative analysis - Edan Leshem; Sara Malone; Andrew Solsrud; Sherry Dodd; Shannon Rook; Sharon Graham; Lauren Ericson; Ruoyun Wang; Katie Plax; Jason Newland (BMC Pediatrics)
Abstract Background Human papillomavirus (HPV), a common sexually transmitted infection in the US, contributes to oropharyngeal and urogenital cancers. To improve HPV vaccine uptake, quality improvement (QI) interventions that address barriers to vaccination in primary care may help. This study aims to understand pediatric primary care providers’ (PCP) perspectives on participating in an HPV QI intervention that utilized practice facilitation to improve HPV vaccine uptake in pediatric primary care clinics. Methods Participants were pediatric PCPs whose clinics completed a QI intervention that utilized practice facilitation led by an outside facilitator. One PCP from each practice completed a 15-min semi-structured exit interview. The interview guide contained questions about PCPs’ experiences during the intervention, skills learned, and thoughts on the use of practice facilitation. Transcribed interviews were analyzed with consensual inductive and deductive techniques. Results Ten participants completed the interview. PCPs had a median experience of 13 years (range: 0–20) in practice, most were female (8/10), white (8/10), and non-Hispanic (9/10). PCPs reported positive experiences and the intervention encouraged them to investigate their current and target vaccination rates more thoroughly. Frequently mentioned practice-wide changes included consistent messaging among all PCPs and staff in a clinic which also extended to other aspects of their care. PCPs liked facilitation and thought that it motivated change. Although they appreciated the flexibility of virtual facilitation meetings with the practice facilitator, they recommended less frequent sessions, focusing some meetings on HPV misinformation, and more support during the intervention (e.g., analyzing data in the context of the practice’s outcomes, communication between participating practices). Conclusion PCPs viewed the facilitation HPV intervention positively. Areas that would improve the intervention include addressing the timing and duration of facilitation sessions, communication strategies, and logistical support (e.g., evidence-based resources for patient education, technological support for data analysis).